2010
DOI: 10.1002/marc.200900578
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High Throughput Method to Investigate Polymer Dissolution

Abstract: The dissolution behavior of polystyrene (PS) in biodiesel was studied by developing a novel high throughput approach based on Fourier-transform infrared (FTIR) microscopy. A multiwell device for high throughput dissolution testing was fabricated using a photolithographic rapid prototyping method. The dissolution of PS films in each well was tracked by following the characteristic IR band of PS and the effect of PS molecular weight and temperature on the dissolution rate was simultaneously investigated. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Among the bands mentioned previously, the vibration of ring quadrant stretching at 1602 cm −1 , which did not overlap with any of the absorption peaks of biodiesel (also shown in Fig. 1), has been used successfully to study the dissolution behavior of PS in biodiesel 11. This band was used as the characteristic signature of the copolymer samples to study their dissolution kinetics in biodiesel.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Among the bands mentioned previously, the vibration of ring quadrant stretching at 1602 cm −1 , which did not overlap with any of the absorption peaks of biodiesel (also shown in Fig. 1), has been used successfully to study the dissolution behavior of PS in biodiesel 11. This band was used as the characteristic signature of the copolymer samples to study their dissolution kinetics in biodiesel.…”
Section: Resultsmentioning
confidence: 92%
“…The trends in the dissolution kinetics obtained from both methods were in excellent agreement; this demonstrated the validity of the high‐throughput FTIR microscopy approach for dissolution testing. Our previous study11 showed that there was a slight discrepancy between FTIR microscopy and gravimetry methods at long dissolution times, and this was attributed to the presence of dissolved mobile polymer in the multiwells in the path of the IR beam, which explained the plateau in the data at less than 100% dissolution. One can easily test large numbers of samples more repeatably with the FTIR microscopy method.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…No commercial systems are available for infrared spectroscopy that can analyze samples in MTP format. However, some systems that operate with 4 * 4 wells have already been published .…”
Section: Spectroscopic Methods For High‐throughput Applicationsmentioning
confidence: 99%